HUKUM JUAL BELI AKUN GAME ONLINE MENURUT PANDANGAN NAHDLATUL ULAMA (NU) DI KABUPATEN MEMPAWAH - Fawaid, Muhammad; Ardiansyah, Ardiansyah; Suhardiman, Suhardiman (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2024)
The focus of this research is to explore the practice of buying and selling online game accounts in Sungai Bakau Besar Darat Village, Mempawah Regency, as well as the legal views of Nahdlatul Ulama (NU) regarding this matter. The research uses a descriptive qualitative approach with a description method to systematically describe existing phenomena. The research location is Sungai Bakau Besar Darat Village, Sungai Pinyuh Sub-district, Mempawah Regency. Data were collected through interviews, observation, and documentation, and analyzed through data reduction, data presentation, conclusion drawing, and verification. The results showed that the practice of buying and selling online game accounts often involves transactions without intermediaries, but is also prone to fraud such as the mismatch of the account sold with the buyer's expectations or the delay in delivery of the account after payment. From NU's perspective, this practice should be considered in accordance with the principles of Islamic muamalah. Although transactions are an important part of social life, they should be in accordance with the flexible teachings of Islam that are grounded in the texts of the Quran and sunnah. Buying and selling in Islamic law is an exchange of wealth that requires moral and ethical considerations in its implementation.